1994
DOI: 10.1002/qua.560520308
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and optical properties of a tin‐encapsulated nickel porphyrazine compound

Abstract: The recently synthesized metal-encapsulated porphyrazine compound, [Sn(r-Bu)2]4-star-Ni(porphyrazine) -Sg , shows very interesting structural and optical absorption features compared with other metal-centered porphyrazines, e.g., metal phthalocyanines (Pc). Using self-consistent-field local density theory, we studied the ground-state and excited-state electronic structure of this molecule and compared it with its metal phthalocyanine analog NiPc. The theoretical optical spectra including oscillator strengths a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Porphyrazines and related molecules have also been a theme of considerable theoretical interest due to their high symmetry, planar atomic arrangements, and electronic delocalization. A large number of theoretical works have been devoted to the understanding of the atomic scale structure of these molecules, their building blocks, and the mechanisms of charge transport and optical properties. , Molecular design of porphyrazines for various Q-band splitting modes has attracted considerable experimental interest, where the ring symmetry modification has been introduced as a new methodology…”
Section: Introductionmentioning
confidence: 99%
“…Porphyrazines and related molecules have also been a theme of considerable theoretical interest due to their high symmetry, planar atomic arrangements, and electronic delocalization. A large number of theoretical works have been devoted to the understanding of the atomic scale structure of these molecules, their building blocks, and the mechanisms of charge transport and optical properties. , Molecular design of porphyrazines for various Q-band splitting modes has attracted considerable experimental interest, where the ring symmetry modification has been introduced as a new methodology…”
Section: Introductionmentioning
confidence: 99%
“…Square-planar complexes, including transition metal porphyrinic complexes, comprise an extremely important class of compounds, being at the center of numerous proteins, enzymes, and one-dimensional conductors. Assignments of the simplest of these complexes, such as tetracyano complexes, have been well established. The more complex porphyrinic complexes have had an accepted assignment of the two principal regions, the Q region in the long visible and the Soret region in the near UV, , but recent calculations have suggested that a change in assignments is appropriate. Polarized electronic spectra have been helpful in making transition assignments, and we have proposed a new set of assignments for metallophthalocyanines (Mpc, where pc = tetraazatetrabenzoporphyrin) using a reduced-symmetry complex and results from earlier SCF-Xα-DOS calculations. …”
mentioning
confidence: 99%
“…[37][38][39][40][41][42][43][44][45] The more complex porphyrinic complexes have had an accepted assignment of the two principal regions, the Q region in the long visible and the Soret region in the near UV, 8,9 but recent calculations have suggested that a change in assignments is appropriate. [46][47][48] Polarized electronic spectra have been helpful in making transition assignments, and * Authors to whom correspondence should be addressed. (1) (a) Franklin and Marshall College.…”
mentioning
confidence: 99%
“…The presence of electron-donating sulfur is expected to shift the absorption range of the porphyrazine Q-band to higher wavelength and tert-butyl groups to enhance solubility [6,12,13,34].…”
Section: Synthesismentioning
confidence: 99%